Position and Implementation of Pancasila Values in National and State Life in Indonesia - Trish, Aurelia; Wijaya, Cherin; Elisa, Elisa; Linardi, Felicia; Hartanty, Valiska Philicia; Angeline, Vanessa; Sitorus, Rolib (Indonesian Journal of Interdisciplinary Research in Science and Technology, 2024)
The descriptions of the position of Pancasila in the Republic of Indonesia are very important to be understood by all Indonesian people, therefore the purpose of this writing is to find out the factors that cause changes in the position and implementation of Pancasila values ​​in the life of the nation and state, and to find out the position of Pancasila as the basis of the state and ideology of the Indonesian nation amidst social, political, and economic developments in Indonesia. In conducting the research, the method used is the normative research method. While the results to be achieved are the factors that influence changes in the position and implementation of Pancasila values ​​in the life of the nation and state are the fading sense of unity and oneness in the nation's ideology caused by the lack of education given to the younger generation which can lead to a lack of knowledge of the state ideology, and the position of Pancasila as the basis of the state and ideology of the Indonesian nation remains relevant amidst dynamic social, political and economic developments. In a social context, Pancasila helps maintain unity and cohesiveness amidst the diversity and pluralism of society.